Low-tack high flame retardant fumed silica and method of making same

CN122898162APending Publication Date: 2026-10-13HUBEI HANGTAI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610847411.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

首先,机械混合法制得的阻燃气相二氧化硅存在组分分散不均匀的问题,阻燃剂与二氧化硅载体之间仅为简单的物理堆积,缺乏有效的相互作用,导致复合材料在长期储存或使用过程中容易发生阻燃剂析出或迁移,不仅影响材料的储存稳定性,还可能导致体系粘度异常增长,严重影响加工工艺性能

Benefits of technology

本发明通过对各组分的巧妙选择与工艺步骤的合理配合,提供了一种兼具极低增粘效应与优异阻燃性能的改性气相二氧化硅体系:气相二氧化硅基体凭借其高比表面积和丰富的纳米孔隙,作为容纳阻燃剂的微观容器,同时在下游高分子材料中发挥基础的力学补强作用;六苯氧基环三磷腈(HPCTP)作为主阻燃剂,在燃烧时能够发挥气相猝灭和凝聚相阻燃的双重作用;聚硼硅氧烷前体在常温下不仅作为HPCTP的载体和固定剂,在高温燃烧时还能转化为陶瓷相前体,为体系提供额外的结构稳定性;疏水修饰剂有效封闭气相二氧化硅外表面的亲水性游离羟基,显著降低粉体的表面能。本发明制备的气相二氧化硅具有独特的“内实外松”结构,在显著降低吸油值(DBP)与混合粘度的同时,完整保留了外部二氧化硅骨架的补强活性,实现了低增粘、高补强与长效阻燃功能的协同统一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898162A_ABST
    Figure CN122898162A_ABST
Patent Text Reader

Abstract

The application discloses a kind of low tackifying high flame-retardant fumed silica and its preparation method, the method utilizes supercritical carbon dioxide as permeation medium, and six phenoxy cyclophosphazene flame retardant is pressed into the nanometer pore of fumed silica with the polysiloxane precursor containing dynamic covalent bond;Through the rheological phase transition of extremely fast pressure relief within 1~5 seconds, the polysiloxane precursor constructs dynamic elastic network in situ in the pore, so as to lock the flame retardant microdroplet physically, and finally the target powder is obtained by surface hydrophobic modification;The powder prepared by the application solves the problem of storage tackiness caused by the easy migration of flame retardant, has excellent stability, the powder has a unique "inner solid outer loose" structure, effectively reduces the oil absorption value and mixing viscosity, while the reinforcing activity of the external silica skeleton is completely retained, realizing the synergistic unity of low tackifying, high reinforcing and long-term flame-retardant function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silica technology, specifically to a low-viscosity, high-resistivity gas-phase silica and its preparation method. Background Technology

[0002] Fumed silica, as an important nanoscale inorganic functional filler, has been widely used in many polymer materials fields such as rubber, plastics, coatings, and adhesives due to its unique three-dimensional network structure, ultra-large specific surface area, and excellent thickening, thixotropic, and reinforcing properties. Especially in organosilicon material systems, fumed silica can not only significantly improve the mechanical strength and temperature resistance of the material, but also enhance its processing performance.

[0003] However, with increasingly stringent requirements for material safety in modern industry, especially in fields such as electronics, construction, and transportation, higher standards have been set for the flame retardant properties of polymer materials. While traditional fumed silica is non-flammable itself, its flame retardant effect is quite limited, and it usually needs to be used in combination with various flame retardants to meet the relevant flame retardant rating requirements.

[0004] Currently, the commonly used flame-retardant fumed silica in existing technologies is mainly prepared through the following methods: First, the simple mechanical mixing method, which involves directly mixing fumed silica with flame retardants; second, the surface chemical grafting method, which involves grafting flame-retardant groups onto the surface of silica through a chemical reaction; and third, the solution impregnation method, which uses organic solvents to load flame retardants onto a silica carrier.

[0005] However, the aforementioned existing technical solutions all have many shortcomings in practical applications: First, the flame-retardant phase silica prepared by mechanical mixing method has the problem of uneven component dispersion. The flame retardant and the silica carrier are only physically stacked and lack effective interaction. This makes the flame retardant prone to precipitation or migration during long-term storage or use of the composite material. This not only affects the storage stability of the material, but may also lead to abnormal increase in the viscosity of the system, which seriously affects the processing performance.

[0006] Secondly, while surface chemical grafting can address the flame retardant migration issue to some extent, this method typically requires prolonged chemical reactions at high temperatures. This process is not only complex and energy-intensive, but also prone to generating byproducts that affect the purity and performance of the final product. More importantly, chemical grafting often consumes the active silanol groups on the surface of fumed silica, weakening its compatibility with the organic matrix and its reinforcing effect.

[0007] Furthermore, traditional solution impregnation methods suffer from problems such as solvent residue and environmental pollution. During solvent evaporation, capillary forces and surface tension can easily lead to uneven distribution of flame retardants on the carrier surface, resulting in agglomeration. This not only reduces flame retardant efficiency but may also block the nanoporous structure of fumed silica, affecting its inherent rheological regulation function.

[0008] Furthermore, existing flame-retardant phase silica products generally suffer from low flame-retardant efficiency. Most products can only exert a single dilution or endothermic flame-retardant mechanism, making it difficult to achieve the synergistic effect of multiple flame-retardant mechanisms. Therefore, a high addition amount is required to achieve the ideal flame-retardant effect, which not only increases costs but may also adversely affect the mechanical and processing properties of the matrix material.

[0009] In summary, developing a modified fumed silica product that retains the original excellent properties of fumed silica, significantly improves its flame retardant effect, and also possesses good storage stability and processing applicability remains a significant technical challenge for those skilled in the art. Therefore, it is urgent to develop new technical solutions to address the aforementioned technical problems in existing technologies. Summary of the Invention

[0010] To address the shortcomings of existing technologies, the present invention aims to provide a low-viscosity, high-resistivity flammable phase silica and its preparation method. The present invention creatively utilizes the mediating properties of supercritical carbon dioxide and combines the dynamic network characteristics of polyborosiloxane precursors to achieve the synergistic effect of in-situ physical locking of flame retardants within the nanopores of flammable phase silica and efficient hydrophobic surface modification.

[0011] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of the present invention provides a method for preparing low-viscosity, high-resistivity gas-phase silica, comprising the following steps: (1) Place fumed silica, hexaphenoxycyclotriphosphazene and polyborosiloxane precursor in a closed pressure-resistant reaction vessel, introduce supercritical carbon dioxide, and carry out constant temperature and pressure permeation treatment under stirring conditions while maintaining the carbon dioxide in a supercritical state at the permeation temperature and permeation pressure. (2) After the constant temperature and pressure permeation treatment is completed, the pressure-resistant reaction vessel is depressurized so that the pressure inside the vessel drops to atmospheric pressure; (3) After the pressure is released, a hydrophobic modifier is added to the pressure-resistant reaction vessel, and the surface modification reaction is carried out under the modification temperature and continuous stirring. After the reaction is completed, the material is discharged to obtain the low-viscosity, high-resistivity gas phase silica.

[0012] Preferably, based on 100 parts by weight of the fumed silica, the amount of hexaphenoxycyclotriphosphazene added is 10-25 parts, the amount of the polyborosiloxane precursor added is 5-15 parts, and the amount of the hydrophobic modifier added is 5-10 parts.

[0013] This invention precisely controls the ratio of the three components to ensure that hexaphenoxycyclotriphosphazene (HPCTP) provides sufficient flame retardant performance, while an appropriate amount of polyborosiloxane precursor forms a gel network within the nanopores of fumed silica that sufficiently encapsulates HPCTP microdroplets. Simultaneously, it retains an appropriate amount of silica surface hydroxyl groups for subsequent grafting reactions with hydrophobic modifiers. If the polyborosiloxane precursor is too small, the network encapsulation will be inadequate, leading to flame retardant leakage and increased viscosity; if too large, it will clog the pores and affect external hydrophobic modification.

[0014] Preferably, the fumed silica is hydrophilic fumed silica with a BET specific surface area of ​​150~300 m² / g. This invention uses hydrophilic fumed silica within this specific surface area range, which has abundant nanopores and suitable pore volume, and a large number of silanol groups (Si-OH) on its surface, providing ample space and reaction sites for the microfoaming filling of flame retardants and subsequent hydrophobic modification.

[0015] Preferably, the polyborosiloxane precursor is liquid at room temperature and has a number-average molecular weight of 500-3000.

[0016] This is the key to the successful pore penetration of this invention. Low molecular weight (500-3000) polyborosiloxane precursors in a room-temperature liquid state exhibit excellent solubility in supercritical carbon dioxide. Under the plasticizing effect of the high-pressure fluid in step (1), their viscosity is further significantly reduced, allowing them to work together with HPCTP as a solute, precisely "carried" into the deepest nanopores of fumed silica by the extremely low surface tension and extremely high diffusion coefficient of supercritical CO2.

[0017] Preferably, in step (1), the infiltration temperature is 60~100℃, the infiltration pressure is 12~20MPa, the isothermal and pressure infiltration treatment time is 1~3h, and the stirring speed is 100~500r / min. These conditions ensure that the carbon dioxide is in a supercritical state, and the dynamic stirring breaks down the mass transfer resistance of the powder, allowing the composite flame retardant carried by the supercritical fluid to uniformly penetrate into the powder particles.

[0018] Preferably, in step (2), the pressure relief control condition is: the pressure inside the pressure-resistant reaction vessel is reduced from the osmotic pressure to atmospheric pressure within 1 to 5 seconds.

[0019] This invention employs an ultra-rapid depressurization process of 1-5 seconds, breaking away from the existing curing mode that relies on high-temperature thermal initiation for cross-linking. During this rapid depressurization, supercritical CO2 rapidly vaporizes and escapes, generating two simultaneous effects: first, supersaturated HPCTP rapidly precipitates within the nanopores, forming microdroplets; second, as the plasticizing effect of CO2 disappears, the Si-OB dynamic covalent bonds in the polyborosiloxane precursor spontaneously recombine, instantly forming a thixotropic elastic gel network within the pores. This network, without requiring high-temperature curing, physically locks the HPCTP microdroplets in situ within the nanopores like a "net," completely solving the problem of free migration of flame retardant molecules during use.

[0020] Preferably, in step (3), the hydrophobic modifier is one of hexamethyldisilazane (HMDS), dimethyldichlorosilane, or octyltrimethoxysilane. These modifiers can undergo efficient condensation reactions with the free silanol groups on the outer surface of fumed silica to form a dense hydrophobic layer.

[0021] Preferably, in step (3), the modification temperature is 120~160℃, the surface modification reaction time is 0.5~2h, and the stirring speed is 100~500r / min.

[0022] Since the core material inside the pores has been locked by the physical elastic network in step (2), the surface modification in step (3) can be carried out at a relatively mild temperature (120~160℃), which effectively avoids the problem of high temperature curing of silicone resin (above 250℃) competing with the outer HMDS modification to consume silanol groups in the prior art, making the outermost hydrophobic end cap more complete, thereby ensuring that the powder has a very low tackification effect in the polymer matrix.

[0023] A second aspect of the present invention provides a low-viscosity, high-resistivity fumed silica prepared by any of the above-described methods. This fumed silica has a ternary composite structure consisting of a matrix, a polyborosiloxane elastic network within nanopores encapsulating flame-retardant microdroplets, and an outer hydrophobic layer.

[0024] A third aspect of the present invention provides the application of the above-mentioned low-viscosity, high-resistivity flame-phase silica in the preparation of flame-retardant polymer materials.

[0025] Preferably, the flame-retardant polymer material includes room temperature vulcanizing (RTV) silicone rubber sealant or polyurethane potting compound. The fumed silica of this invention, added as a filler to the aforementioned polymer material, not only does not significantly increase the viscosity of the base adhesive system (i.e., low viscosity increase) due to its densely packed internal pores and excellent hydrophobicity of the outer surface, but also, when the material is exposed to combustion (e.g., >600°C), the polyborosiloxane network within the pores undergoes an in-situ ceramization reaction, generating a high-temperature resistant SiBOC ceramic phase. This ceramic microparticle sintersects and fuses with the silica framework, forming a continuous and robust supporting carbon layer at the combustion interface. Combined with the vapor-phase quenching mechanism of HPCTP, this greatly improves the limiting oxygen index (LOI) and flame-retardant rating of the polymer material.

[0026] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a modified fumed silica system with both extremely low thickening effect and excellent flame retardant properties through the ingenious selection of components and the rational coordination of process steps: the fumed silica matrix, with its high specific surface area and abundant nanopores, serves as a microscopic container for flame retardants, while also playing a fundamental mechanical reinforcing role in downstream polymer materials; hexaphenoxycyclotriphosphazene (HPCTP), as the main flame retardant, can exert a dual role of gas-phase quenching and condensed-phase flame retardancy during combustion; the polyborosiloxane precursor not only serves as a carrier and fixative for HPCTP at room temperature, but can also be transformed into a ceramic phase precursor during high-temperature combustion, providing additional structural stability to the system; the hydrophobic modifier effectively seals the hydrophilic free hydroxyl groups on the outer surface of the fumed silica, significantly reducing the surface energy of the powder. The fumed silica prepared by this invention has a unique "solid inside and loose outside" structure. While significantly reducing the oil absorption value (DBP) and mixed viscosity, it fully retains the reinforcing activity of the external silica skeleton, achieving a synergistic unity of low viscosity increase, high reinforcement and long-lasting flame retardant function.

[0027] This invention provides a modified fumed silica system that combines extremely low viscosity, high reinforcement, and excellent long-lasting flame retardant properties. Through ingenious component design and supercritical fluid processing, this invention endows fumed silica with a unique "solid inside, loose outside" structure, achieving a perfect synergistic unity of low viscosity, high reinforcement, and flame retardant functions.

[0028] In conventional processes, the low-molecular-weight flame retardant within the pores tends to migrate outwards, leading to an increase in system viscosity. High-temperature sealing, on the other hand, consumes surface silanol groups, affecting hydrophobic modification. This invention perfectly resolves this contradiction through supercritical carbon dioxide-carried component co-infiltration and rapid depressurization within 1-5 seconds. During the rapid depressurization, the rapid escape of carbon dioxide causes the polyborosiloxane precursor to instantly transform into a highly viscous gel deep within the pores, firmly "freezing" HPCTP. Due to the excellent dimensional and thermodynamic matching between HPCTP's unique rigid ring structure and the PBS elastic network, its physical locking is extremely strong. This deep filling occupies the internal cavity, significantly reducing the powder's absorbent polymer (DBP) value and preventing the polymer matrix from penetrating—this is the "internal solidity." Simultaneously, this physical locking eliminates the need for high-temperature baking, completely preserving the free silanol groups on the outer surface, allowing for thorough subsequent hydrophobic modification. The complete elimination of surface polarity breaks the hydrogen bond network between particles, significantly reducing surface energy—this is the "external looseness." This "solid inside, loose outside" configuration completely cuts off the migration path of the flame retardant, achieving long-lasting and extremely low viscosity while fully preserving the excellent reinforcing activity of the external silicon skeleton.

[0029] Typically, silica treated with phosphorus-containing flame retardants tends to form loose ash after high-temperature combustion, resulting in limited improvement in the limiting oxygen index (LOI). However, the material prepared in this invention does not form loose ash during combustion; instead, it forms an in-situ crust, creating a dense and continuous ceramic-like protective layer, resulting in a significant non-linear increase in LOI. This unexpected effect is due to the fact that the polyborosiloxane precursor pre-filled in the "solid" pores not only acts as a carrier at room temperature but also, even at temperatures exceeding the polymer decomposition temperature (>600℃), does not completely volatilize but undergoes in-situ sintering and high-temperature phase transformation with the external silica framework, generating an ultra-high-temperature resistant Si-BOC ceramic phase. Compared to conventional liquid flame retardants that foam and destroy the carbon layer upon heating, this hard ceramic phase strongly supports the combustion interface macroscopically, effectively inhibiting polymer collapse and dripping. Furthermore, it forms a dual-channel synergistic flame retardant mechanism with the phosphorus-containing quenching free radicals released by HPCTP, combining physical barrier properties of the ceramic phase with chemical quenching in the gas phase, achieving flame retardant performance far exceeding the expectations of a single component. Attached Figure Description

[0030] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some schematic diagrams of certain embodiments of the present invention, and therefore should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 The low-viscosity, high-resistivity gas-phase silica prepared in Example 1 of this invention; Figure 2The infrared spectrum of the low-viscosity, high-resistivity gas-phase silica prepared in Example 1 of this invention; Figure 3 This is a set of contact angle data for a certain group of low-viscosity, high-resistivity gas-phase silica prepared in Example 1 of the present invention. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Of course, the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0033] Unless otherwise specified, all chemical reagents and materials in this invention are purchased from the market or synthesized from raw materials purchased from the market.

[0034] 1. Hydrophilic fumed silica: The HIFULL® series hydrophilic fumed silica powder produced by Hubei Huifu Company was used.

[0035] The model corresponding to BET with a specific surface area of ​​150 m² / g is HL-150; the model corresponding to BET with a specific surface area of ​​200 m² / g is HL-200; and the model corresponding to BET with a specific surface area of ​​300 m² / g is HL-300.

[0036] 2. Hexaphenoxycyclotriphosphazene (HPCTP): Industrial grade, purity ≥99.0%, white crystalline powder at room temperature.

[0037] The melting point ranges from 110℃ to 112℃, with a phosphorus content of approximately 9.0 wt% and a nitrogen content of approximately 4.0 wt% (as in commercially available products from Zhejiang Wansheng Co., Ltd. or similar manufacturers). This substance exhibits good solubility in supercritical CO2 and readily precipitates upon depressurization.

[0038] 3. Polyborosiloxane precursor (PBS): It is a transparent viscous liquid at room temperature (25℃), and is prepared by the condensation reaction of boric acid and low molecular weight terminal hydroxyl silicone oil. The main chain skeleton contains "Si-OB" dynamic covalent bonds.

[0039] The reagents used in the examples have number-average molecular weights of 500, 1000, and 3000 (which can be controlled by changing the reactant ratio and polymerization time, or customized from a supplier of organosilicon specialty chemicals). Due to their low molecular weight characteristics, they exhibit extremely low viscosity in the supercritical state.

[0040] 4. Conventional silicone oil (for comparative substitution): Conventional methyl-terminated polydimethylsiloxane (PDMS): Dow Corning PMX-200 series silicone oil is used. It is a colorless and transparent liquid at room temperature. The product with a kinematic viscosity of about 10~20 cSt is selected (its number average molecular weight Mn is about 1000).

[0041] 5. Conventional flame retardants (for comparative replacement): Bisphenol A bis(diphenyl phosphate) (BDP): Industrial grade, colorless to pale yellow transparent slightly viscous liquid at room temperature, phosphorus content of about 8.9 wt%, acid value ≤0.1 mg KOH / g (commercially available conventional halogen-free organophosphorus flame retardant).

[0042] 6. Surface hydrophobic modifier: Hexamethyldisilazane (HMDS), dimethyldichlorosilane (DDS), and octyltrimethoxysilane (OTMS): all are analytical grade (purity ≥99.0%) and are transparent liquids at room temperature.

[0043] 7. Carbon dioxide gas: Industrial high-purity carbon dioxide, purity ≥99.99%, supplied by standard steel cylinders, water content ≤20ppm.

[0044] 8. Silicone rubber base and additives for application performance testing: RTV base rubber: Commercially available 107 room temperature vulcanizing silicone rubber (hydroxyl-terminated polydimethylsiloxane) is selected. It is a transparent viscous liquid at room temperature with a dynamic viscosity of 5000 mPa·s (25℃).

[0045] Crosslinking agent: Tetraethyl orthosilicate (TEOS), analytical grade.

[0046] Catalyst: Dibutyltin dilaurate (DBTDL), analytical grade.

[0047] This invention provides a method for preparing low-viscosity, high-resistivity gas-phase silica, the general operation process of which is as follows: Step (1) Supercritical permeation treatment: Accurately weigh 100 parts by weight of fumed silica, 10-25 parts by weight of hexaphenoxycyclotriphosphazene (HPCTP), and 5-15 parts by weight of polyborosiloxane precursor. The fumed silica is preferably hydrophilic with a BET specific surface area in the range of 150-300 m² / g; the polyborosiloxane precursor is liquid at room temperature and its number-average molecular weight is controlled between 500 and 3000.

[0048] The above materials were placed together in a sealed, pressure-resistant reaction vessel equipped with a stirrer. After sealing, carbon dioxide gas was introduced into the vessel, and the system temperature was adjusted to the permeation temperature of 60-100℃ and the system pressure to the permeation pressure of 12-20 MPa, so that the carbon dioxide in the vessel reached and was maintained in a supercritical state. At this temperature and pressure, the stirrer was turned on, and the stirring speed was set at 100-500 r / min. The constant temperature and pressure permeation treatment was carried out for 1-3 hours to allow the HPCTP and polyborosiloxane precursor dissolved in the supercritical fluid to fully enter the nanopores of the fumed silica.

[0049] Step (2) Rapid pressure relief network locking: After the isothermal and pressure osmosis treatment in step (1) is completed, the aeration is stopped. By controlling the pressure relief valve, the pressure inside the pressure-resistant reaction vessel is rapidly reduced from the above-mentioned osmosis pressure (12~20MPa) to atmospheric pressure within 1~5 seconds. During this rapid reduction, supercritical carbon dioxide rapidly vaporizes and escapes, causing the polyborosiloxane precursor that has entered the pores to undergo a rheological phase transition, forming a network structure and physically locking the simultaneously precipitated HPCTP microdroplets in situ.

[0050] Step (3) Surface hydrophobic modification: After depressurization and restoration of atmospheric pressure within the container, 5-10 parts by weight of a hydrophobic modifier are added to the pressure-resistant reaction vessel. The hydrophobic modifier is selected from any one of hexamethyldisilazane, dimethyldichlorosilane, or octyltrimethoxysilane. The system temperature is adjusted to the modification temperature of 120-160°C, and the surface modification reaction is carried out under continuous stirring at a speed of 100-500 r / min for 0.5-2 h. After the reaction is complete, the material is devolatilized to obtain the low-viscosity, high-resistivity, gas-phase silica of this invention.

[0051] The modified fumed silica powder prepared by the above general preparation method can be used as a functional filler and is widely used in the preparation of flame-retardant polymer materials (especially flame-retardant room temperature vulcanizing silicone rubber sealants or flame-retardant polyurethane potting compounds). While imparting excellent flame-retardant properties to the substrate (improving the limiting oxygen index), it maintains extremely low initial viscosity of the system and excellent storage and placement stability.

[0052] The present invention will be further described below through specific embodiments.

[0053] Example 1 This embodiment provides a method for preparing low-viscosity, high-resistivity gas-phase silica, the specific steps of which are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g), 15g of hexaphenoxycyclotriphosphazene (HPCTP), and 10g of polyborosiloxane precursor (number average molecular weight of 1000) that is liquid at room temperature. Place the above materials in a 2L sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, raise the temperature and pressure, and set the system osmosis temperature to 80℃ and the osmosis pressure to 15MPa (at which point the carbon dioxide is in a supercritical state). Turn on the stirring and set the speed to 300r / min. Perform osmosis treatment for 2h under these constant temperature and pressure conditions.

[0054] (2) Rapid pressure relief network locking: After the permeation treatment is completed, stop the introduction of carbon dioxide. Quickly and completely open the pressure relief valve of the reactor, and reduce the pressure in the reactor from 15MPa to atmospheric pressure within 3 seconds to complete the micro-droplet precipitation of flame retardant and the in-situ network locking of polyborosiloxane precursor.

[0055] (3) Surface hydrophobic modification: After depressurization and stabilization of the pressure inside the reactor, 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1 hour at a stirring speed of 300r / min. After the reaction was completed, small molecule byproducts were removed by vacuuming, and the material was cooled and discharged to obtain the low-viscosity, high-resistivity, and gas-phase silica powder, such as... Figure 1 As shown, its infrared spectrum is as follows Figure 2 As shown in the figure, the contact angle experimental data is as follows: Figure 3 As shown.

[0056] Example 2 This embodiment provides a method for preparing low-viscosity, high-resistivity gas-phase silica, the specific steps of which are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​150m² / g), 10g of hexaphenoxycyclotriphosphazene, and 5g of polyborosiloxane precursor (number average molecular weight of 500) that is liquid at room temperature. Place the above materials in a sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, set the system osmosis temperature to 60℃, and the osmosis pressure to 12MPa. Turn on the stirring and set the speed to 100r / min. Perform osmosis treatment for 3h under these constant temperature and pressure conditions.

[0057] (2) Rapid pressure relief network locking: After the permeation treatment is completed, stop the gas supply. Quickly open the pressure relief valve to reduce the pressure in the reactor from 12MPa to atmospheric pressure within 1 second.

[0058] (3) Surface hydrophobic modification: After depressurization and stabilization of the reactor, 5g of dimethyldichlorosilane was added to the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 120℃, and the surface modification reaction was carried out for 2 hours at a stirring speed of 100r / min. After the reaction was completed, the by-products were removed by vacuuming, and the product was cooled and discharged to obtain the target powder.

[0059] Example 3 This embodiment provides a method for preparing low-viscosity, high-resistivity gas-phase silica, the specific steps of which are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​300m² / g), 25g of hexaphenoxycyclotriphosphazene, and 15g of polyborosiloxane precursor (number average molecular weight of 2000) that is liquid at room temperature. Place the above materials in a sealed pressure-resistant reactor. Introduce carbon dioxide gas, set the system osmosis temperature to 100℃, and the osmosis pressure to 20MPa. Start stirring, set the speed to 500r / min, and carry out osmosis treatment for 1h under constant temperature and pressure conditions.

[0060] (2) Rapid pressure relief network locking: After the permeation treatment is completed, stop the gas supply. Quickly open the pressure relief valve and reduce the pressure in the reactor from 20MPa to atmospheric pressure within 5 seconds.

[0061] (3) Surface hydrophobic modification: After depressurization and stabilization of the reactor, 10g of octyltrimethoxysilane was added to the reactor as a hydrophobic modifier. The temperature inside the reactor was adjusted to the modification temperature of 160℃, and the surface modification reaction was carried out for 0.5h at a stirring speed of 500r / min. After the reaction was completed, the target powder was obtained by discharging the material.

[0062] Example 4 This embodiment provides a method for preparing low-viscosity, high-resistivity gas-phase silica, which involves replacing the upper limit of the molecular weight of the polyborosiloxane precursor. The specific steps are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g), 15g of hexaphenoxycyclotriphosphazene (HPCTP), and 10g of polyborosiloxane precursor (number average molecular weight of 3000) that is liquid at room temperature. Place the above materials in a 2L sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, raise the temperature and pressure, and set the system osmosis temperature to 80℃ and the osmosis pressure to 15MPa. Turn on the stirring and set the speed to 300r / min. Perform osmosis treatment for 2h under these constant temperature and pressure conditions.

[0063] (2) Rapid pressure relief network locking: After the permeation treatment is completed, stop the introduction of carbon dioxide. Quickly and completely open the pressure relief valve of the reactor, and reduce the pressure in the reactor from 15MPa to atmospheric pressure within 3 seconds.

[0064] (3) Surface hydrophobic modification: After depressurization and stabilization of the pressure inside the reactor, 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1h at a stirring speed of 300r / min. After the reaction was completed, small molecule byproducts were removed by vacuuming, and the material was cooled and discharged to obtain the low-viscosity, high-resistivity, gas-phase silica.

[0065] Comparative Example 1 This comparative example provides a method for preparing modified fumed silica, which uses ordinary silicone oil without dynamic covalent bonds for equal-volume replacement. The specific steps are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g), 15g of hexaphenoxycyclotriphosphazene (HPCTP), and 10g of conventional methyl-terminated polydimethylsiloxane (PDMS, number average molecular weight of 1000). Place the above materials in a 2L sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, raise the temperature and pressure, and set the system osmosis temperature to 80℃ and the osmosis pressure to 15MPa. Turn on the stirring and set the speed to 300r / min. Perform osmosis treatment for 2h under these constant temperature and pressure conditions.

[0066] (2) Rapid pressure relief network locking: After the permeation treatment is completed, stop the introduction of carbon dioxide. Quickly and completely open the pressure relief valve of the reactor, and reduce the pressure in the reactor from 15MPa to atmospheric pressure within 3 seconds.

[0067] (3) Surface hydrophobic modification: After depressurization and stabilization of the pressure inside the reactor, 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1h at a stirring speed of 300r / min. After the reaction was completed, small molecule byproducts were removed by vacuuming, and the product was cooled and discharged to obtain the modified powder.

[0068] Comparative Example 2 This comparative example provides a method for preparing modified fumed silica, using a conventional liquid phosphorus-based flame retardant for equal-volume replacement. The specific steps are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g), 15g of conventional liquid phosphate flame retardant bisphenol A bis(diphenyl) phosphate (BDP), and 10g of polyborosiloxane precursor (number average molecular weight of 1000) that is liquid at room temperature. Place the above materials in a 2L sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, raise the temperature and pressure, and set the system osmosis temperature to 80℃ and the osmosis pressure to 15MPa. Turn on the stirring and set the speed to 300r / min. Perform osmosis treatment for 2h under these constant temperature and pressure conditions.

[0069] (2) Rapid pressure relief network locking: After the permeation treatment is completed, stop the introduction of carbon dioxide. Quickly and completely open the pressure relief valve of the reactor, and reduce the pressure in the reactor from 15MPa to atmospheric pressure within 3 seconds.

[0070] (3) Surface hydrophobic modification: After depressurization and stabilization of the pressure inside the reactor, 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1h at a stirring speed of 300r / min. After the reaction was completed, small molecule byproducts were removed by vacuuming, and the product was cooled and discharged to obtain the modified powder.

[0071] Comparative Example 3 This comparative example provides a method for preparing modified fumed silica, which uses a conventional organic solvent impregnation method to replace the supercritical permeation and rapid depressurization process of the present invention. The specific steps are as follows: (1) Conventional solvent permeation treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g), 15g of hexaphenoxycyclotriphosphazene (HPCTP), and 10g of polyborosiloxane precursor (number average molecular weight of 1000) that is liquid at room temperature. Dissolve HPCTP and polyborosiloxane precursor completely in 500mL of anhydrous ethanol to form a homogeneous solution. Then add fumed silica to the solution and stir continuously at room temperature for 2h at a speed of 300r / min.

[0072] (2) Slowly evaporate the solvent: After stirring, transfer the mixture to a vacuum oven at 80°C and evaporate the ethanol solvent under slow vacuum conditions until the powder reaches constant weight.

[0073] (3) Surface hydrophobic modification: After the solvent is completely removed, the obtained powder is placed in a reaction vessel, and 8g of hexamethyldisilazane (HMDS) is sprayed into it. The temperature inside the vessel is raised to the modification temperature of 140℃, and the surface modification reaction is carried out for 1h at a stirring speed of 300r / min. After the reaction is completed, the by-products are removed by vacuuming, and the material is cooled and discharged to obtain the modified powder.

[0074] Comparative Example 4 This comparative example provides a method for preparing modified fumed silica and verifies the effect of slow pressure release on lock-in. The specific steps are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g), 15g of hexaphenoxycyclotriphosphazene (HPCTP), and 10g of polyborosiloxane precursor (number average molecular weight of 1000) that is liquid at room temperature. Place the above materials in a 2L sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, raise the temperature and pressure, and set the system osmosis temperature to 80℃ and the osmosis pressure to 15MPa. Turn on the stirring and set the speed to 300r / min. Perform osmosis treatment for 2h under these constant temperature and pressure conditions.

[0075] (2) Slow pressure relief treatment: After the permeation treatment is completed, stop the introduction of carbon dioxide. Use the fine adjustment of the pressure relief valve to slowly relieve the pressure, and control the pressure in the reactor to gradually and steadily drop from 15MPa to atmospheric pressure within 30 minutes (i.e., without triggering the instantaneous rheological phase change caused by rapid vaporization).

[0076] (3) Surface hydrophobic modification: After depressurization and stabilization of the pressure inside the reactor, 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1h at a stirring speed of 300r / min. After the reaction was completed, small molecule byproducts were removed by vacuuming, and the product was cooled and discharged to obtain the modified powder.

[0077] Comparative Example 5 This comparative example provides a method for preparing modified fumed silica, which uses the supercritical process of this invention to load only flame retardants, but does not add any polyborosiloxane precursors. The specific steps are as follows: (1) Supercritical osmosis treatment: Accurately weigh 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g) and 15g of hexaphenoxycyclotriphosphazene (HPCTP), without adding any polyborosiloxane precursors. Place the above materials in a 2L sealed pressure-resistant reactor equipped with a stirring device. Introduce carbon dioxide gas into the reactor, raise the temperature and pressure, and set the system osmosis temperature to 80℃ and the osmosis pressure to 15MPa. Turn on the stirring and set the speed to 300r / min. Perform osmosis treatment for 2h under these constant temperature and pressure conditions.

[0078] (2) Rapid pressure relief treatment: After the permeation treatment is completed, stop the introduction of carbon dioxide. Quickly and completely open the pressure relief valve of the reactor, and reduce the pressure in the reactor from 15MPa to atmospheric pressure within 3 seconds (due to the lack of precursor, this step can only achieve the precipitation of flame retardant and cannot form network locking).

[0079] (3) Surface hydrophobic modification: After depressurization and stabilization of the pressure inside the reactor, 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The temperature inside the reactor was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1h at a stirring speed of 300r / min. After the reaction was completed, small molecule byproducts were removed by vacuuming, and the product was cooled and discharged to obtain the modified powder.

[0080] Comparative Example 6 This group provides a pure fumed silica with only conventional hydrophobic modification as an absolute blank benchmark for basic physicochemical properties and flame retardant properties. The specific preparation steps are as follows: 100g of hydrophilic fumed silica (BET specific surface area of ​​200m² / g) was accurately weighed, without the addition of any flame retardants or polyborosiloxane precursors. This silica powder was directly placed into a 2L sealed reactor equipped with a stirrer. 8g of hexamethyldisilazane (HMDS) was sprayed into the reactor as a hydrophobic modifier. The reactor temperature was raised to the modification temperature of 140℃, and the surface modification reaction was carried out for 1 hour at a stirring speed of 300r / min. After the reaction, small molecule byproducts were removed by vacuuming, and the material was cooled and discharged to obtain conventionally hydrophobically modified blank fumed silica powder.

[0081] Blank group This group provides an unmodified hydrophilic fumed silica (BET specific surface area of ​​200 m² / g).

[0082] To fully verify the technical advantages of the low-viscosity, high-resistivity gas phase silica prepared by this invention and the synergistic mechanism between the components / processes, the powders prepared in the above examples and comparative examples were used as fillers for application performance evaluation.

[0083] 1. Preparation of experimental samples To avoid interference from the cross-linking curing reaction on the viscosity test, this experiment completely separated the preparation of the viscosity test sample from that of the flame retardant test strip: Viscosity test matrix preparation (without crosslinking agent / catalyst): Take 100 parts by weight of room temperature vulcanized (RTV) hydroxyl-terminated polydimethylsiloxane (base gel, viscosity about 5000 mPa·s), add 10 parts by weight of the modified silica powder prepared in the above groups, and stir evenly under vacuum conditions. It can be used directly for viscosity evaluation.

[0084] Flame retardant test strip preparation (including crosslinking agent / catalyst): Add 5 parts by weight of KH560 and 0.5 parts by weight of organotin catalyst to the above mixed adhesive. After vacuum degassing, inject into the mold and use calendering to assist in molding to ensure that the cured strip is dense and free of bubbles, and the thickness is strictly controlled within 3.2±0.1mm.

[0085] 2. Testing Methods (1) Oil absorption value: The oil absorption value of each sample in dibutyl phthalate was determined according to ASTM D2414 standard.

[0086] (2) Using a contact angle measuring instrument (JY-82B or equivalent), deionized water was used as the test solution to measure the surface contact angle of each sample powder after it was pressed into a tablet under a pressure of 20MPa. The average value was taken at 5 different locations for each sample.

[0087] (3) Initial viscosity: The initial viscosity was recorded after equilibration at 25℃ for 30 minutes using an NDJ-8S rotational viscometer (rotor No. 4, speed 6r / min).

[0088] (4) Long-term storage viscosity: The rubber compound was sealed and placed under constant temperature of 25°C. After 30 days and 180 days, it was taken out and cooled to equilibrium, and the viscosity was measured under the same conditions.

[0089] (5) Limiting Oxygen Index (LOI): Tested according to GB / T2406.2-2009 standard.

[0090] (6) UL-94 vertical flammability rating: tested according to GB / T2408-2021 standard.

[0091] (7) Objective criteria for macroscopic char formation morphology: Observe the char residue after combustion, apply pressure of about 5N with tweezers. If it does not crush or collapse, it is recorded as "hard ceramic phase", if it is easily broken, it is recorded as "fragile and loose carbon layer", and if it is scattered with the airflow, it is recorded as "loose ash".

[0092] The test results are shown in Tables 1 and 2.

[0093] Table 1. Test results of low viscosity enhancement properties Table 2 Flame retardant performance test results The low viscosity-increasing and high flame-retardant effects of the fumed silica of this invention are not a simple physical superposition of the components, but rather a unique product resulting from the highly synergistic effect of supercritical fluid phase change, the dynamic network of polyborosiloxane (PBS), HPCTP precipitation, and the ultra-rapid depressurization process. The analysis is as follows, based on the data in Tables 1 and 2: In Comparative Example 5 (without PBS precursor) and Comparative Example 1 (replaced with ordinary silicone oil without dynamic crosslinking ability), during rapid depressurization (1-5 seconds), the vaporized CO2 blows out a large amount of un-network-locked HPCTP or liquid silicone oil from the pores to the outer surface of the gaseous silicone. This severe surface contamination directly masks the silanol groups, causing large-area failure of subsequent HMDS hydrophobic modification, with contact angles plummeting to 118° and 108°. Due to the unresolved surface polarity and the presence of viscous organic matter, their initial viscosities both surged to 35500 mPa·s and 42000 mPa·s, completely losing their "low viscosity increase" characteristics.

[0094] In Examples 1-4, the rapid depressurization caused the supercritical plasticizing effect to disappear instantly. The Si-OB dynamic covalent bonds unique to the PBS precursor underwent a rheological phase transition deep within the pores, spontaneously reorganizing into a strong and resilient elastic gel network. This instantaneously cross-linked "net" strongly resisted the purging force of CO2 escape, firmly "freezing" the simultaneously supersaturated and precipitated HPCTP particles deep within the pores. Precisely because the flame retardant was not blown out, the free silanol groups on the outer surface of the gaseous silica were 100% intact, resulting in extremely thorough subsequent hydrophobic modification (contact angle reaching 135-142°, comparable to the purely hydrophobic comparative example 6).

[0095] Remarkably, the initial mixing viscosity of Examples 1-4 (18500-21500 mPa·s) was significantly lower than that of Comparative Example 6 (25200 mPa·s), which contained no flame retardants and underwent only hydrophobic modification. This unexpectedly low viscosity-increasing effect is the pinnacle of the synergistic effect of "solid inside and loose outside". Although Comparative Example 6 has a hydrophobic surface, its nanopores are hollow (DBP as high as 275 mL / 100 g), and the base adhesive molecular chains inevitably penetrate into the pores, increasing the hydrodynamic volume of the particles. In contrast, the PBS and HPCTP in the examples were locked inside the pores, completely preventing the penetration of the polymer matrix and reducing the frictional resistance between the filler and the matrix to an extremely low value.

[0096] Comparative Example 4, by simply changing the depressurization time to a slow 30-minute depressurization, failed to achieve instantaneous cross-linking of the gel due to missing the phase transition trigger window caused by rapid vaporization. The slowly leaking liquid components not only degraded the initial viscosity (31500 mPa·s) but also continued to leak out during 180 days of thermodynamic aging, causing the viscosity to surge to 58000 mPa·s. In contrast, the perfectly synergistic example group showed extremely stable viscosity after 180 days (only a slight increase to approximately 20000 mPa·s), confirming that the gel-locking network completely severed long-term migration pathways.

[0097] Compared to Comparative Example 5 (with HPCTP alone) and Comparative Example 2 (with conventional flame retardant BDP), the LOI hovered only around 26.0-26.8%, with the char residue crumbling upon light touch. However, in Examples 1-4, with the same small absolute addition amount, the LOI nonlinearly jumped to 30.0-31.5%, successfully achieving the V-0 level. This phenomenon, which breaks through the conventional dose-response bottleneck, is also attributed to the "solid" structure formed by the three components synergistically: the PBS gel pre-filled and confined within the nanopores did not volatilize, but instead underwent an in-situ synergistic phase transformation with the coated HPCTP and the external silica framework at a high temperature >600°C, sintering to form a dense Si-BOC ceramic phase resistant to ultra-high temperatures. This hard armor grown in situ at the combustion interface effectively inhibits the collapse of the matrix droplets, and, combined with the gaseous quenching free radicals released by HPCTP, achieves flame retardant performance far exceeding that of a single component.

[0098] The success of this invention is not due to arbitrary combinations of flame retardants and gels. The complete failure of Comparative Example 2 (which replaced HPCTP with an equal amount of conventional liquid flame retardant BDP) profoundly reveals the irreplaceable rheological-scale synergy and high-temperature thermodynamic synergy between HPCTP and the PBS network. The PBS precursor forms a dynamic elastic network during the rapid decompression. HPCTP has a large-volume rigid hexaphenoxycyclotriphosphazene ring structure, which perfectly matches the pore size and thermodynamic polarity of the PBS network. Once trapped, it completely loses its migration ability. Therefore, the viscosity of Example 1 remains stable after 180 days. In contrast, in Comparative Example 2, BDP is a normal-temperature flexible liquid chain macromolecule. Its non-rigid conformation is very easy to escape from the pores of the PBS network under long-term thermodynamic drive, resulting in initial leakage and complete loss of viscosity control after 180 days.

[0099] At high-temperature combustion interfaces exceeding 600°C, conventional liquid flame retardant BDP undergoes violent decomposition and foaming upon heating, releasing a large amount of volatile gases. This boiling and scouring behavior directly disrupts the cross-linking and ceramicization process that PBS and the silica framework should be undergoing, resulting in Comparative Example 2 ultimately forming only a fragile, loose char residue with numerous airflow pores, causing the LOI to drop to 26.8%. In contrast, the HPCTP in this invention, upon heating, undergoes a gentle, multi-element in-situ cross-linking process with the Si-OB framework of PBS, forming a hard, continuous ceramic protective layer, significantly increasing the LOI to 30.2%.

[0100] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing low-viscosity, high-resistivity gas-phase silica, characterized in that, Includes the following steps: (1) Place fumed silica, hexaphenoxycyclotriphosphazene and polyborosiloxane precursor in a closed pressure-resistant reaction vessel, introduce supercritical carbon dioxide, and carry out constant temperature and pressure permeation treatment under stirring conditions while maintaining the carbon dioxide in a supercritical state at the permeation temperature and permeation pressure. (2) After the constant temperature and pressure permeation treatment is completed, the pressure-resistant reaction vessel is depressurized so that the pressure inside the vessel drops to atmospheric pressure; (3) After the pressure is released, a hydrophobic modifier is added to the pressure-resistant reaction vessel, and the surface modification reaction is carried out under the modification temperature and continuous stirring. After the reaction is completed, the material is discharged to obtain the low-viscosity, high-resistivity gas phase silica.

2. The preparation method according to claim 1, characterized in that, Based on 100 parts by mass of the fumed silica, the amount of hexaphenoxycyclotriphosphazene added is 10-25 parts, the amount of the polyborosiloxane precursor added is 5-15 parts, and the amount of the hydrophobic modifier added is 5-10 parts.

3. The preparation method according to claim 1, characterized in that, The fumed silica is hydrophilic fumed silica with a BET specific surface area of ​​150~300m² / g.

4. The preparation method according to claim 1, characterized in that, The polyborosiloxane precursor is liquid at room temperature and has a number-average molecular weight of 500-3000.

5. The preparation method according to claim 1, characterized in that, In step (1), the permeation temperature is 60~100℃, the permeation pressure is 12~20MPa, the time for the constant temperature and pressure permeation treatment is 1~3h, and the stirring speed is 100~500r / min.

6. The preparation method according to claim 1, characterized in that, In step (2), the pressure relief control condition is to reduce the pressure inside the pressure-resistant reaction vessel from the osmotic pressure to atmospheric pressure within 1 to 5 seconds.

7. The preparation method according to claim 1, characterized in that, In step (3), the hydrophobic modifier is one of hexamethyldisilazane, dimethyldichlorosilane or octyltrimethoxysilane.

8. The preparation method according to claim 1, characterized in that, In step (3), the modification temperature is 120~160℃, the surface modification reaction time is 0.5~2h, and the stirring speed is 100~500r / min.

9. A low-viscosity, high-resistivity gas-phase silica prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the low-viscosity, high-resistivity flame-phase silica according to claim 9 in the preparation of flame-retardant polymer materials.